The changing of bioethical conscience - Precondition for permanent global peace and sustainable development - Donev, Dejan (Pultusk Academy of Humanities, 2013)
The basic request of the 21st century is building sustainable Peace and development. But, the 21st century can be also the century of wars and unpredicted economic development caused by two reasons: first, if we don’t find a solution for the global warming as a result of ecologically unsustainable production; second, because of the shortage of the base of life - water, which natural cycle of reproduction is fundamentally endanger from many reasons. To avoid all this it’s necessary to fill up more preconditions: changing the ethics of understanding of others cultures and civilizations; changing the current ways on material reproduction which violating the basic human rights on peaceful and healthy life with the effects on the global clime changes; but first of all, we must change our bioethical conscience as a precondition for permanent global peace and sustainable development! That makes ecology, economics and bioethics the main fields through which the relations in the world today will be resolved for the future. This means that we must make changes in the production to avoid the world wide ecological disaster. In another words, this requests totally new conception of global economy which will be released from political interests and desires for domination. That will produce base for equal quality of life for every human been. Ultimate result of that will be (bio)ethics of life through which we will avoid any possible conflicts of interest which are always the main reason for wars.
Keywords: bioethics, peace, understanding, conscience